Implementasi Data Mining Penjualan Produk Kosmetik Pada PT. Habasa Natural Menggunakan Regresi Linear Sederhana - Haikal Bahrul Saputra (Jejaring Penelitian dan Pengabdian Masyarakat (JPPM), 2025)
Women’s lives are generally inseparable from the use of cosmetics, which not only serve to enhance appearance but also to maintain skin and body health, making them one of the basic needs with ever-increasing demand. PT. Habasa Natural, as a producer and seller of natural cosmetics, experiences daily growth in sales transactions, resulting in an ever-expanding volume of stored data. However, most of this data is merely archived without being optimally utilized, even though it contains valuable insights such as consumer purchasing patterns, the most popular products, and relationships between products that are often bought together. By properly leveraging sales data, the company can develop more effective marketing strategies, such as creating product bundles, offering special promotions, or arranging strategic product placement, enabling data-driven business decisions to improve operational efficiency, competitiveness, and customer satisfaction.